2008
DOI: 10.1590/s0102-09352008000200010
|View full text |Cite
|
Sign up to set email alerts
|

Urethral duplication in a dog: case report

Abstract: A male Brazilian Fila dog was referred because of a perineal orifice with urine stream during micturition. To determine the extent of the accessory channel, a contrasted retrograde urethrocystography was performed. A surgical correction was undertaken. Histological study showed the presence of the urethral channel lined by multilayer transitional epithelium. The patient recovered well and there was no evidence of complications one year after surgery.Keywords: dog, urethra, surgery, urinary, micturition RESUMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
(9 reference statements)
1
10
0
Order By: Relevance
“…In this case report, the dog presented a Y-type duplication (type IIA2), complete, with external communication (6,7). The classification proposed by Effmann et al (7) acknowledges three types of duplications for humans, latter adapted in one previous case report (8). Type I includes blind, incomplete urethral duplications, and type II include complete urethral duplications.…”
Section: Discussionmentioning
confidence: 74%
“…In this case report, the dog presented a Y-type duplication (type IIA2), complete, with external communication (6,7). The classification proposed by Effmann et al (7) acknowledges three types of duplications for humans, latter adapted in one previous case report (8). Type I includes blind, incomplete urethral duplications, and type II include complete urethral duplications.…”
Section: Discussionmentioning
confidence: 74%
“…Two confirmed cases of incomplete urethral duplication with no external opening (Duffey et al, 1998;Palm et al, 2015) and two confirmed cases of complete duplication (Tobias and Barbee, 1995;Stedile et al, 2008) have been reported in dogs.…”
Section: Abstract: Dog; Urethral Duplication; Dermoid Cyst; Urolithiasismentioning
confidence: 78%
“…Urethral duplication can be described as complete if the diverticulum has an external opening (Bello, 2014) or incomplete if the diverticulum is blind ended (Anderson et al, 1980;Lawrence et al, 1983). Only four cases of urinary duplication have been described in the veterinary literature (Tobias and Barbee, 1995;Duffey et al, 1998;Stedile et al, 2008;Palm et al, 2015). To the authors' knowledge, neither urolithiasis nor dermoid cyst has ever been reported in association with urethral duplication.…”
Section: Abstract: Dog; Urethral Duplication; Dermoid Cyst; Urolithiasismentioning
confidence: 97%
See 1 more Smart Citation
“…Urethral duplication is a rare congenital anomaly infrequently diagnosed in domestic animal species. A total of five cases of urethral duplication have been reported in veterinary medicine, with four cases reported in dogs [1,2,3,4]. Urethral duplication may be complete with communication to the skin surface or may be incomplete and end blindly.…”
Section: Introductionmentioning
confidence: 99%